2020
DOI: 10.3389/fmicb.2019.03109
|View full text |Cite
|
Sign up to set email alerts
|

Shifts Between and Among Populations of Wheat Rhizosphere Pseudomonas, Streptomyces and Phyllobacterium Suggest Consistent Phosphate Mobilization at Different Wheat Growth Stages Under Abiotic Stress

Abstract: Climate change models predict more frequent and prolonged drought events in Central Europe, which will exert extraordinary pressure on agroecosystems. One of the consequences is drought-related nutrient limitations for crops negatively affecting agricultural productivity. These effects can be mitigated by beneficial plant growth promoting rhizobacteria. In this study, we investigated the potential of cultivable bacterial species for phosphate solubilization in the rhizosphere of winter wheat at two relevant gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 102 publications
1
14
0
1
Order By: Relevance
“…Both community structure and its trait composition are steered by various environmental factors. Vegetation cover (Francioli et al, 2018) and plant growth stage (Wang et al, 2016;Breitkreuz et al, 2020), as well as soil moisture dynamics, alter composition and traits of soil and plant rhizosphere communities prominently (De Vries et al, 2012;Santos-Medellín et al, 2017;Ochoa-Hueso et al, 2018). Moreover, Lauber et al (2008) found that the microbial community structure is strongly affected by soil type, a finding that was further supported by a study comparing soil bacteria as well as fungi-dominated food webs across various European field sites (de Vries et al, 2013).…”
Section: Introductionmentioning
confidence: 83%
“…Both community structure and its trait composition are steered by various environmental factors. Vegetation cover (Francioli et al, 2018) and plant growth stage (Wang et al, 2016;Breitkreuz et al, 2020), as well as soil moisture dynamics, alter composition and traits of soil and plant rhizosphere communities prominently (De Vries et al, 2012;Santos-Medellín et al, 2017;Ochoa-Hueso et al, 2018). Moreover, Lauber et al (2008) found that the microbial community structure is strongly affected by soil type, a finding that was further supported by a study comparing soil bacteria as well as fungi-dominated food webs across various European field sites (de Vries et al, 2013).…”
Section: Introductionmentioning
confidence: 83%
“…Using a metabarcoding approach, we monitored responses of the bacterial community associated with different wheat compartments (rhizosphere and root) to flooding stress. Since plant phenology is an important driver in plant microbiota assembly (Donn et al, 2015;Francioli et al, 2018), and abiotic stress might affect differentially the plant-microbiota complex depending on the specific plant growth stage (PGS) in which it occur (Na et al, 2019;Breitkreuz et al, 2020), we imposed flooding stress only once, either at tillering, booting or flowering. Moreover, several soil and plant traits were measured through the whole experiment to correlate edaphic and physiological plant changes with shifts in bacterial community assemblage.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we investigated the potential of cultivable bacterial species for phosphate solubilization in the rhizosphere of winter wheat. Wheat stem elongation stage was associated with a high abundance of Pseudomonas , but also at the grain filling stage with Phyllobacterium [ 65 ]. Since the members of the clusters 1 and 2 also responded to PCC, both plant-derived compounds and changes in soil properties and temperature may play out in the differential seasonal distribution of this group.…”
Section: Discussionmentioning
confidence: 99%